HUBUNGAN KEBIASAAN MAKAN DAN PRAKTIK KEBERSIHAN DIRI DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS SIKUMANA KOTA KUPANG - Ni Putu Intan Suseni; Florentianus Tat; Herliana Monika Azi Djogo (CHMK HEALTH JOURNAL, 2022)
Introduction: Stunting or short is a condition of failure to thrive in infants (0-11 months) and children under five (12-59) months. The condition of stunting indicates insufficient nutrition for a long time, so it is very important to fulfill adequate nutrition at an early age. Purpose: This study was to determine the relationship between eating habits and personal hygiene practices with the incidence of stunting in children under five in the working area of ​​the Sikumana Community Health Center, Kupang City. Methods: the research design used was analytical correlation with a "cross sectional" approach. The sample in this study were 124 parents who have children aged 2-5 years who were selected using the simple random sampling technique. The data were collected using a questionnaire on eating habits and personal hygiene practices and the height of the children was measured using a microtoise and converted into a standard value (z-score). Results: inappropriate eating habits (66.9%), and poor personal hygiene practices (71%) with an incidence of stunting (71.8%), Chi Square test results on eating habits showed ρ value = 0.002 , which means there is a relationship between eating habits and the incidence of stunting in children under five in the working area of ​​the Sikumana Community Health Center, Kupang City, in personal hygiene practices ρ value = 0.003, which means that there is a relationship between personal hygiene practices and the incidence of stunting in children under five in the working area of ​​the Sikumana Community Health Center, Kupang City. Conclusion: there is a relationship between eating habits and personal hygiene practices with the incidence of stunting in children under five in the Sikumana Community Health Center, Kupang City. Suggestion: in this case parents must know, be able and aware of the importance of health for both mother and child, especially paying attention to eating habits and personal hygiene practices in children Keywords: Eating Habits, Personal Hygiene Practices, Incidence of Stunting